Pengaruh Brand Trust dan Brand Image terhadap Loyalitas Nasabah dalam Menggunakan Asuransi Jiwa pada Ajb Bumiputera 1912 Medan - Hayani, Nur Syamsidah; Rahma, Tri Inda Fadhila; Nasution, Juliana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The high growth of service companies in Indonesia encourages companies to attract the hearts of their customers in order to become loyal customers of the company's products, one of the service companies that continues to grow in Indonesia is a service company in the insurance sector. Where life insurance is now seen as important and necessary in everyday life. One alternative approach that is widely used by companies is to create brand trust and the company's brand image to gain customer loyalty. This study aims to determine the effect of brand trust and brand image partially or simultaneously on customer loyalty in using life insurance at Ajb Bumiputera 1912 Medan. The method used in this study uses a quantitative method by taking 89 respondents from selected customers as research samples through probability sampling technique with calculations using the slovin formula. The questionnaire uses hypothesis testing with SPSS version 25 software and uses linear data using multiple linear regression analysis methods. The results of this study simultaneously from the variable brand trust (X1) and brand image (X2) have a positive and significant effect on customer loyalty. And partially the variables brand trust (X1) and brand image (X2) also have a positive and significant effect on customer loyalty in using life insurance. Keywords : Brand Trust, Brand Image, Customer Loyalty, Life Insurance.